A simple flow cytometry method improves the detection of phosphatidylserine‐exposing extracellular vesicles - Arraud, N.; Gounou, C.; Linares, R.; Brisson, A. R. (Journal of thrombosis and haemostasis, 2015)
Summary Background Plasma contains cell‐derived extracellular vesicles (EVs), which participate in physiopathological processes and have potential applications as disease biomarker. However, the enumeration of EVs faces major problems, due to their sub‐micrometer size and to intrinsic limitations in methods of characterization, mainly flow cytometry (FCM). Objectives Our objective is to enumerate EVs in plasma, by taking as the prototype the population of phosphatidylserine (PS)‐exposing EVs, which constitute one of the major EV populations and are responsible for thrombotic disorders. Methods The concentration of PS‐exposing EVs in platelet‐free plasma (PFP) of healthy subjects was measured by FCM using either light scattering or fluorescence as the trigger and fluorescent Annexin‐5 (Anx5) as the specific label. In addition, PS‐exposing EVs were enumerated by electron microscopy (EM) after labeling with Anx5 gold nanoparticles and sedimentation on EM grids. Results We show that about 50× more Anx5‐positive EVs are detected by FCM when detection is triggered on fluorescence as compared with light scattering. By fluorescence triggering, concentrations of 22 000–30 000 Anx5‐positive EVs per μL PFP were determined, using two different flow cytometers. The limit of detection of the fluorescence triggering method was estimated at about 1000–2500 Anx5 molecules. Results from EM suggest that EVs down to 100–150 nm diameter are detected by fluorescence triggering. Conclusion This study presents a simple method for enumerating EVs. We believe that this method is applicable in a general context and will improve our understanding of the roles of EVs in pathophysiological situations, which will open avenues for the development of EV‐based diagnosis assays.